2016
DOI: 10.1136/tobaccocontrol-2016-053014
|View full text |Cite
|
Sign up to set email alerts
|

What are kids vaping? Results from a national survey of US adolescents

Abstract: Objective To examine what substances U.S. youth vape. Methods Data come from Monitoring the Future, an annual, nationally-representative survey of U.S. 12th, 10th, and 8th grade students. Respondents reported what substance they vaped the last time they used a vaporizer such as an e-cigarette. Results Among students who had ever used a vaporizer, 65–66% last used “just flavoring” in 12th, in 10th, and in 8th grade, more than all other responses combined. In all three grades the percentage using “just flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 18 publications
4
109
4
Order By: Relevance
“…The present study's finding suggests that the remaining majority of users have used e-cigarettes to consume nicotine. In contrast, a recent study using a different self-reported measure found that between 13% and 22% of students in grades 8, 10, and 12 who had ever used an e-cigarette reported using nicotine the last time they had used an e-cigarette (10). In the present analysis, it is unknown whether students who had used an e-cigarette for a non-nicotine substance had also used an e-cigarette for nicotine, which might underestimate nicotine use.…”
Section: Discussionmentioning
confidence: 72%
“…The present study's finding suggests that the remaining majority of users have used e-cigarettes to consume nicotine. In contrast, a recent study using a different self-reported measure found that between 13% and 22% of students in grades 8, 10, and 12 who had ever used an e-cigarette reported using nicotine the last time they had used an e-cigarette (10). In the present analysis, it is unknown whether students who had used an e-cigarette for a non-nicotine substance had also used an e-cigarette for nicotine, which might underestimate nicotine use.…”
Section: Discussionmentioning
confidence: 72%
“…The development of such evidence for the direct effects of e-cigarettes may require many years or even decades (as it did for regular cigarettes), and once this body is developed e-cigarette manufacturers could change their ingredients and the process may need to start all over again. In addition, recent research shows that the majority of youth who vape report that they vape ‘just flavouring’ and not nicotine 22. Consequently, regulations and policies based on a rationale of nicotine regulation may not necessarily apply to youth e-cigarette use in a straightforward way.…”
Section: Discussionmentioning
confidence: 99%
“…One reason why nicotine vaping may have been more common in the current sample is that participants in this study were all past 30-day vapers who were asked what nicotine concentration they typically vaped over the past 30-days, whereas the Monitoring the Future study assessed the substance vaped in the most recent episode. 13 Since youth alternate use of different e-liquids 34 that may or may not contain nicotine, nicotine vapers may not necessarily have vaped an e-cigarette containing nicotine during their most recent vaping occasion, which would result in lower nicotine vaping prevalence estimates than assessing the substance typically vaped. Alternatively, the participants in this study were all from California, and it is possible that California adolescent e-cigarette users may vape nicotine at higher rates than national samples.…”
Section: Discussionmentioning
confidence: 99%